EVALUASI PENILAIAN KAPASITAS SISA JEMBATAN LAWANG TADJI - N. Retno Setiati; Setyo Hardono (Direktorat Bina Teknik Jalan dan Jembatan, 2006)
Bridge is transportation infrastructure and connection of some areas, either in land, sea, river, or mountain have to fulfill planning criteria. Among bridge planning criteria a i.e. standard of strength, inertia, stability, security, and ride ability. Assessment of bridge residual value or capacities are very important in a scheme of repair and bridge rehabilitation, or whether a bridge is properly used or not. The girder of bridge in general one with slab of bridge. Therefore, the approach used to calculate capacities of cross section is T girder. Capacity of T girder is evaluated with ultimate strength concept. This theory has proven through experiment by many experts, and close to actual condition.